Climate-smart cotton (Gossypium herbaceum) crop production in Punjab: A comprehensive review of sustainable management practices - DHIR, ABHISHEK; PAL, R K; KINGRA, P K; KAUR, RAMANJIT (The Indian Journal of Agricultural Sciences, 2024)
The growth and productivity of cotton (Gossypium herbaceum L.) crop are greatly influenced by major fluctuations in the local weather. The output of cotton is negatively impacted by extended periods of unfavourable weather, despite the crop's apparent relative resistance to heat and drought. Among various cotton growing states in India, Gujarat often leads as the highest cotton-producing state in the country followed by Maharashtra, Telangana, Rajasthan, Karnataka and Andhra Pradesh. These states collectively contribute more than 65% to India's cotton production. In Punjab, the optimal sowing window for cotton spans from the 1stApril to 15th May. Deviating from this recommended time frame, be it through excessively early or late sowing, correlates with compromised crop establishment and reduced productivity. Temperature thresholds dictate progression of the cotton crop's key stages. For germination, a threshold temperature of 16°C is required, while the range of 21 to 27°C is conducive to vegetative growth, and 27 to 32°C supports reproductive development. The diurnal/night time temperature for fostering cotton root growth resides within 30°C/22°C to 35°C/27°C. Elevated temperatures (40°C/32°C), even under adequate water and nutrient conditions, results in the emergence of shallow root systems. Strategic measures encompassing suitable sowing dates, precise plant spacing, favourable row orientations, judicious irrigation techniques and mulching can effectively temper the influence of climate change on cotton output. Furthermore, the application of crop simulation models and access to timely, accurate weather forecasts and agro-advisories equips decision-makers with invaluable insights for short-term operational planning.